FAR-LATERAL TRANSCONDYLAR APPROACH - R. N. Lyunkova; P. A. Lopanchuk; A. V. Gushchin; E. A. Mishurinskaya; V. A. Bendosenko; V. V. Krylov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Surgical treatment of craniospinal disorders and craniovertebral junction disorders is one of the most challenging problems in neurosurgery, because the pathological process involves the brain stem, cerebellum, cranial nerves of the cerebellopontine angle (CPA), spinal nerves, vertebral artery (VA) and its branches, basilar artery (BA) and its branches, bone structures, as well as joints and ligaments of the craniovertebral junction. Various approaches are used to get the access to the craniovertebral junction and foramen magnum, including the far-lateral approach analyzed in this article. The choice of surgical approach depends on the spread of pathological process.